Lipid mediator serum profiles in asthmatics significantly shift following dietary supplementation with omega‐3 fatty acids. Issue 8 (4th July 2013) - Lundström, Susanna L.; Yang, Jun; Brannan, John D.; Haeggström, Jesper Z.; Hammock, Bruce D.; Nair, Parameswaran; O'Byrne, Paul; Dahlén, Sven‐Erik; Wheelock, Craig E.; Schneider, Claus
<x xml:space="preserve">Abstract</x> Scope In contrast to well‐characterized PUFA levels in serum, little is known regarding their downstream metabolic products. However, many of these compounds are lipid mediators with prominent roles during pro‐ and antiinflammatory processes. Methods and results In this double blind crossover study on asthmatics, shifts in serum levels of ω‐3 and ω‐6 PUFA‐derived oxidized fatty acids (e.g. eicosanoids, oxylipins) were quantified following dietary fish oil supplementation. Serum was obtained from subjects following fasting at three occasions; (i) prior to supplementation, (ii) following a 3‐week supplement intake of either placebo or fish oil, and (iii) following a 3‐week washout period with a subsequent 3‐week period of either fish oil or placebo supplement. A total of 87 oxylipins representing cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP) metabolic pathways were screened via LC‐MS/MS. The primary alterations observed were in CYP‐ and 15‐LOX‐derived EPA‐ and CYP‐derived DHA oxylipins. Conclusion The results indicate that intake of an ω‐3 rich diet alters not only the PUFA ratio, but also the ratio of downstream oxylipins. These data further support that dietary manipulation with ω‐3 PUFAs affects not only PUFA levels, but importantly also the downstream metabolic profile.